Towards information of communication and linguistics competences to form knowledge society - Ruiz Durán, Graciela (2007)
Within a Society of knowledge and information, different competences for everyone are required without considering those deep gaps that pull us apart; development, poverty, social exclusion, digital and intercultural gaps, etc. Among those required competences we can underline, cognitive, linguistic and communicative competenccs which lead to constitute: reading competence, oral and writing expression, basic competences above which the future of general knowledge is built. In relation to the competences already mentioned , Peru is occupying the last place among 43 countries in Program for Internacional Student Assessment (PISA), made by the Organization for Economic Co-operation and Development OECD. Although the Assessment Ministry has started and emergency Plan to overcome chat situation, we should consider necessary a complete confronting from governmental policy; a deepening of communication and education conceptual frame, according to the new tendency of Clinical Pedagogy, implementation and development of a Nacional Educacional project  2021, presented by the Nacional Council of Education, considered and assumed by the current government, the reference and research development about this subject, as the one made in Colombia, and particularly, the importance of initial and continuing training for teachers, supported on profiles and standards